Exercise-induced mobilization of white blood cells in breast cancer patients - Koivula, Tiia (My University, 2023)
Acute exercise causes mobilization of the immune cells in healthy individuals, but the phenomenon is less investigated in cancer patients. Exercise-induced mobilization of leukocytes may have positive effects in cancer patients by improving the ability of the immune system to combat against tumor cells. Thus, the objective of this study was to examine how 30-minute acute exercise alters the number of circulating leukocytes in breast cancer patients. Blood samples were drawn at rest, at 15-minute (E15) and at 30-minute (E30) time points during the exercise, and 30 minutes and 60 minutes post-exercise, and used for quantification of total leukocytes and different leukocyte subsets using flow cytometry. Acute exercise increased the number of total leukocytes, neutrophils, lymphocytes, monocytes, basophils, total T cells, CD4+ T cells, T helper (Th) 1 cells, Th 2 cells, Th 17 cells, CD8+ T cells, CD4-CD8- T cells, CD56+ natural killer (NK) cells, and CD14-CD16+ monocytes (p<0.05 in all). Heart rate and heart rate percentage of age-predicted maximal heart rate correlated positively with monocyte and basophil mobilization at E15. Moreover, lactate concentration correlated positively with lymphocyte and NK cell mobilization at E30. Cancer grade correlated positively with basophil mobilization at E15 and with increase in neutrophils and decrease in myeloid derived suppressor cells between baseline and E30. The findings show that 30-minute acute exercise increases the number of several leukocyte subsets in breast cancer patients. The mobilization of some leukocytes appears to be related to the intensity of exercise and the disease state.
Keywords: breast cancer, exercise, immunology, white blood cells